2007
DOI: 10.1007/s00261-007-9267-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast enhanced magnetic resonance imaging of the terminal ileum: differentiation of activity of Crohn’s disease

Abstract: D-CE-MRI can be a useful tool for clinical follow-up and in the treatment strategies in CD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 21 publications
3
63
0
2
Order By: Relevance
“…Several studies have also shown that the MRI technique defines not only the site but also the degree of CD activity, by evaluating the increased enhancement of the involved bowel wall by means of contrast T1-weighted sequences. [6][7][8][9][10][11][12] Horsthuis et al performed a meta-analysis and reported that there was no statistically significant difference between MRI and CT in the detection of inflammatory bowel disease, including extra-enteric complications. 13 The retroperitoneal abscess is a relatively rare condition and is often misdiagnosed or even recognized late in the clinical course.…”
Section: Consentmentioning
confidence: 99%
“…Several studies have also shown that the MRI technique defines not only the site but also the degree of CD activity, by evaluating the increased enhancement of the involved bowel wall by means of contrast T1-weighted sequences. [6][7][8][9][10][11][12] Horsthuis et al performed a meta-analysis and reported that there was no statistically significant difference between MRI and CT in the detection of inflammatory bowel disease, including extra-enteric complications. 13 The retroperitoneal abscess is a relatively rare condition and is often misdiagnosed or even recognized late in the clinical course.…”
Section: Consentmentioning
confidence: 99%
“…Several later studies emphasized the usefulness of MR in distinguishing patients with active disease from those with inactive disease (4)(5)(6)(7)(8)(9)(10). However, the current issue is whether MRI is able to grade the severity of the disease in the same way as other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, other studies have demonstrated a correlation between MRE and CDAI (33,46,47) and a correlation between MRE and laboratory markers of inflammation (erythrocyte sedimentation rate/C-reactive protein) (41-43). Only two pediatric studies compared MRE to PCDAI, one demonstrating a statistically significant correlation between disease on MRE and PCDAI (48) and the other demonstrating no correlation between MRE and PCDAI (49).…”
Section: Comparison Of Mre To Disease Activity Indexmentioning
confidence: 99%